(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Ten brands of cosmetics were randomly purchased from shops in Dar es Salaam, and were subjected to microbiological assessment for microbial quality, preservative capacity and identification of microbial contaminants. Aliquots of each cosmetic were uniformly spread-plated on agar plates to quantify, isolate and identify microbial contaminants using conventional microbiological methods. The cup-plate technique complemented by the dilution test was used for evaluation of cosmetic preservative capacity. Microbial contaminants were present in 70% of the cosmetics. The most frequently isolated and identified microbial contaminants were attributable to Proteus mirabilis, Staphylococcus aureus, Bacillus and Trichophyton species. The cosmetics displayed inadequate preservative capacity evidenced by inability to lower the inherent bio-burdens to acceptable levels and to inhibit growth of the tested microorganisms. Such products can have detrimental effects on health status of consumers as consequence of their altered stability profiles and secondary microbial infections. Therefore, microbiological quality control of cosmetics available in the Tanzanian market should be re-enforced.